1998
DOI: 10.1084/jem.188.8.1433
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-derived 5′-Adenosine Monophosphate Promotes Endothelial Barrier Function via CD73-mediated Conversion to Adenosine and Endothelial A2B Receptor Activation

Abstract: During episodes of inflammation, polymorphonuclear leukocyte (PMN) transendothelial migration has the potential to disturb vascular barrier function and give rise to intravascular fluid extravasation and edema. However, little is known regarding innate mechanisms that dampen fluid loss during PMN-endothelial interactions. Using an in vitro endothelial paracellular permeability model, we observed a PMN-mediated decrease in endothelial paracellular permeability. A similar decrease was elicited by cell-free super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
242
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(253 citation statements)
references
References 53 publications
11
242
0
Order By: Relevance
“…CD73 is a key regulator of extracellular ATP metabolism and inflammation as it shifts the balance from pro-inflammatory ATP and prothrombotic ADP to anti-inflammatory adenosine by converting AMP into adenosine. Adenosine is a known anti-inflammatory agent, which promotes endothelial integrity and has neuroprotective properties [17,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD73 is a key regulator of extracellular ATP metabolism and inflammation as it shifts the balance from pro-inflammatory ATP and prothrombotic ADP to anti-inflammatory adenosine by converting AMP into adenosine. Adenosine is a known anti-inflammatory agent, which promotes endothelial integrity and has neuroprotective properties [17,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…CD73 modulates the extent of immune and inflammatory responses in vitro and in vivo. These effects are mediated via its enzymatic capability to hydrolyse adenosine monophosphate 5 0 -AMP into adenosine, an immunomodulatory purine compound [16][17][18].We have recently shown that CD73 is upregulated on vascular endothelium in a time-and dose-dependent manner after treatment with type-I IFN-a in vitro and in vivo [19], but how IFN-b affects CD73 in brain EC and in the context of MS has never been studied before. As adenosine, the end product of the CD73 catalytic reaction, has both anti-inflammatory and neuroprotective effects, we hypothesized that IFN-b might also exert some of its beneficial effects on MS-disease pathology by regulating CD73-mediated adenosine production.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that nucleotides used for purinergic regulation of macrophages at an inflammatory locus are released from other cells, such as neutrophils, damaged tissues, or bacteria. Neutrophils have been reported to release relatively high amounts of nucleotides during activation by formyl peptides (45). A recent study also described the release of ATP from J774 macrophage cultures infected with Mycobacterium tuberculosis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Guibert et al (1998) reported that inhibition of ectonucleotidase activity reduced the A 2A -AdoR-mediated dilation of endothelium-denuded portal vein strips caused by ATP. Similarly, inactivation of ectonucleotidase by monoclonal antibodies reduced the A 2B -AdoRmediated decrease of endothelial permeability caused by adenine nucleotides (Lennon et al, 1998). Furthermore, administration of the ecto-5'-nucleotidase inhibitor AOPCP reduced the formation of adenosine from exogenously administered ATP by the isolated perfused guinea-pig heart (Borst & Schrader, 1991).…”
Section: Mechanism Of a 2a -Ador Activation By Atpmentioning
confidence: 94%